(3QSGdI aj GdWHs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3GdHGH ai eJaY TLQI GdJGQjN heG jNQL efgG gi TLQI eYQaI hbTQgG MGQ jGHS s
(3BNQgG (B:s
(3ddTbjbg hGdVQHGf hGdOhNg dLejY eG jMOK ai GdQCS ef GdChLGY s
(3QJHgG Ydi HGH hNGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B92 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP eMeO GdXGgQ Hf YGThQ (B_ (3JhfS s
Keywords: (3GdWHs